ANALISIS PERKEMBANGAN PENGUASAAN TEKNIK DASAR BOLA VOLI PADA MAHASISWA PENDIDIKAN KEPELATIHAN OLAHRAGA UNIMED MELALUI PEMBELAJARAN PRAKTIK - Hashemi Rafsanjani; Fitri Fadila Hasibuan; Muhammad Rizky Hutabarat; Jovan Atmananda Sinambela; Luga Marcelino Sinaga; Paulus Siagian; Dewi Endriani (STKIP Subang, 2026)
Mastery of basic techniques is a fundamental aspect of volleyball learning. Basic techniques including underhand passing, overhead passing, smash, service, and blocking are essential skills that must be possessed by students of Sports Coaching Education as prospective educators and sports coaches. This study aimed to analyze the development of volleyball basic technique mastery among Sports Coaching Education students through practical learning. The study employed a qualitative descriptive approach using observation methods. The research subjects were Sports Coaching Education students of the 2025 cohort enrolled in the Basic Volleyball Skills course at the Faculty of Sports Science and Health, Universitas Negeri Medan. Data were collected through direct observation during fourteen learning sessions. The results indicated improvements in all observed technical aspects. Underhand passing and overhead passing developed more rapidly than other techniques, while smash and blocking required longer adaptation periods due to their complex movement coordination demands. Factors contributing to skill improvement included systematic training, consistent movement repetition, proper technical demonstrations, and the use of video-based learning media. The findings suggest that structured practical learning effectively enhances students' mastery of volleyball basic techniques in a gradual and sustainable manner.